Gingivitis as a risk factor in periodontal disease - Lang, Niklaus P.; Schätzle, Marc A.; Löe, Harald (Journal of clinical periodontology, 2009)
Background: Dental plaque has been proven to initiate and promote gingival inflammation. Histologically, various stages of gingivitis may be characterized prior to progression of a lesion to periodontitis. Clinically, gingivitis is well recognized. Material & Methods: Longitudinal studies on a patient cohort of 565 middle class Norwegian males have been performed over a 26‐year period to reveal the natural history of initial periodontitis in dental‐minded subjects between 16 and 34 years of age at the beginning of the study. Results: Sites with consistent bleeding (GI=2) had 70% more attachment loss than sites that were consistenly non‐inflamed (GI=0). Teeth with sites that were consistently non‐inflamed had a 50‐year survival rate of 99.5%, while teeth with consistently inflamed gingivae yielded a 50‐year survival rate of 63.4%. Conclusion: Based on this longitudinal study on the natural history of periodontitis in a dentally well‐maintained male population it can be concluded that persistent gingivitis represents a risk factor for periodontal attachment loss and for tooth loss.